CORPORATE SOCIAL RESPONSIBILITY, INTELLECTUAL CAPITAL, DAN KINERJA KEUANGAN: EKSPLORASI MODEL - Lina Lina (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
This study aims to explore a model based on the following research questions: (1) Does corporate social responsibility/CSR affect financial performance? (2) Does corporate social responsibility affect intellectual capita/ICl? (3) Does intellectual capital affect financial performance? (4) Does corporate social responsibility affect financial performance through intellectual capital. CSR has a positive influence on financial performance. Based on the four propositions put forward, the following conclusions are obtained. CSR activity is the first step to identify the impact of corporate sustainability in creating better business opportunities. By increasing CSR activities carried out by the company, it will improve the performance produced by IC and produce effective and efficient company internal processes with the implementation of governance and management systems based on sustainability. The company carries out CSR activities with the aim of improving financial performance and making CSR a component in the formulation of corporate strategy that aims to increase the company's internal resources or intellectual capital on an ongoing basis.